Anatomically corrected malposition of the great arteries: two case reports - Erkut Öztürk; Ender Ödemiş; Öykü Tosun; Yakup Ergül; Alper Güzeltaş (KARE Publishing, 2014)
Anatomically corrected malposition of the great arteries (ACMGA) is defined as parallel arising of aorta and main pulmonary artery (PA) roots although ventriculoarterial connection is normal. Abnormally related aorta arises from the left ventricle, while abnormally related PA arises from the right ventricle. It can be diagnosed with via echocardiography. In some cases, additional imaging modalities such as computerized tomographic angiography and magnetic resonance are required. In this article, we presented two cases of ACMGA, 5-month-old boy and 1-month-old girl. We wanted to point out the importance of differential diagnosis of other great artery anomalies from this rare pathology.